2011
DOI: 10.3390/en4081129
|View full text |Cite
|
Sign up to set email alerts
|

Water Transfer Characteristics during Methane Hydrate Formation Processes in Layered Media

Abstract: Gas hydrate formation processes in porous media are always accompanied by water transfer. To study the transfer characteristics comprehensively, two kinds of layered media consisting of coarse sand and loess were used to form methane hydrate in them. An apparatus with three PF-meter sensors detecting water content and temperature changes in media during the formation processes was applied to study the water transfer characteristics. It was experimentally observed that the hydrate formation configurations in di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…It was observed that pore size is the most important parameter affecting hydrate equilibrium conditions compared to the adsorption mechanism in clays, mineral components, and surface texture of minerals. In the study of Zhang et al, hydrate was formed in sediments having two layers: coarse sand (1–2 mm particle size) and loess (very fine sediment deposits: 0.0345 mm particle size). Two layers of coarse sands bounding a layer of loess and two loess layers bounding a layer of coarse sand were used in different hydrate formation experiments.…”
Section: Theorymentioning
confidence: 99%
“…It was observed that pore size is the most important parameter affecting hydrate equilibrium conditions compared to the adsorption mechanism in clays, mineral components, and surface texture of minerals. In the study of Zhang et al, hydrate was formed in sediments having two layers: coarse sand (1–2 mm particle size) and loess (very fine sediment deposits: 0.0345 mm particle size). Two layers of coarse sands bounding a layer of loess and two loess layers bounding a layer of coarse sand were used in different hydrate formation experiments.…”
Section: Theorymentioning
confidence: 99%